Factors associated with using GPS in road accidents at Cotonou in 2019. - MAKOUTODE, CODJO ABODOURIN ALBERT CHARLES PATRICK; KPOZEHOUEN, ALPHONSE; GANDJI, LAURELLE GLORIA; GLELE AHANHANZO, YOLAINE; Sopoh, Ghislain Emmanuel (My University, 2022)
Introduction: Precise spatial location of accidents is relevant for accidentol-ogy researches or road safety investigations. Objective: The aim of this study is to investigate a number of factors associated with the geolocation of road accidents in the city of Cotonou in 2019. Methods: It was a cross-sectional, retrospective study with an analytical focus. Results: This study highlighted a prevalence of coordinates of the GPS reported at 41.63% in 2019 relating to the files of accidents on public roads during the period from April 18 to June 12, 2020. The work was carried out from 384 accident files examined in the 6 districts of Cotonou selected randomly. A logistic regression made it possible to sort out associated factors with using GPS in road accidents. The final model retained through the “ascending step by step” modeling was adopted. The average age of the responsible agents in charge of the observation was around 32 years (32.13 ± 3.17). Geolocation identified associated factors were: the level of instruction with odd Ratio 2 and its 95% confidence interval f [1.02 - 2.40], the means of conveyance odd ratio 2.56 and its 95% confidence interval of [1.21 - 5.41], the severity level of the accident with its odd ratio 4.59 and its 95% confidence interval of [2.82 - 8.32], and the type of day on which the ac-cident occurred with odd ratio 0.56 and its 95% confidence interval f [0.437 - 2.553]. As for the quality of the reported GPS coordinates, 85% of them were good quality. Conclusion: The reduction of road accidents, given its serious nature and extent, requires strategies to promote geolocation of accidents to ensure better identification of risk areas and decision-making adapted to the accident phenomenon.
Keywords: Accidents; GPS; Geolocation